Sleep Less, Weigh More: Unraveling the Sleep-Obesity Connection in Adult - Az’yan Nazwa Maharani Putri; Rahmah Dwi Yuliyanti; Almira Sitasari; Agus Wijanarka; Jutharat Attawet; Tri Siswati (Ficco Scientific Corner, 2025)
Background: Obesity is an increasingly complex and common global health problem, especially among adults. The aim of this scoping review is to examine the relationship between sleep duration and obesity in adults. Methods: A scoping review was conducted following the Joanna Briggs Institute (JBI) methodology guideline. Databases including PUBMED, ScienceDirect, DOAJ, and ResearchGate were searched in 2024 with the keywords